2017
DOI: 10.1002/jor.23720
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically stimulated biomarkers signal cartilage changes over 5 years consistent with disease progression in medial knee osteoarthritis patients

Abstract: Using serum biomarkers to assess osteoarthritis (OA) disease state and risks of progression remain challenging. This study tested the hypothesis that changes to serum biomarkers in response to a mechanical stimulus in patients with medial knee OA signal cartilage thickness changes 5 years later. Specifically, serum concentrations of a collagen degradation marker (C1,2C) and a chondroitin sulfate synthesis marker (CS846) were measured 0.5 and 5.5 hours after a 30-min walk in 16 patients. Regional cartilage thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…Individuals with lesser biomechanical loading on the ACLR limb at the 6-month follow-up exam, compared to the contralateral limb, demonstrated greater concentrations of plasma MMP-3 and IL-6, as well as serum type-II collagen turnover, indicating early interactions between mechanical joint loading and metabolic processes that may influence the future breakdown of cartilage and future KOA onset. In a small intervention study (n ¼ 16), changes to serum level of C1,2C and CS846 in response to a 30-min walk in patients with medial KOA was evaluated 52 . Regional cartilage thickness changes were measured from MRI obtained at study entry and at 5-year follow-up.…”
Section: Understanding the Biology Of Joint Deteriorationmentioning
confidence: 99%
“…Individuals with lesser biomechanical loading on the ACLR limb at the 6-month follow-up exam, compared to the contralateral limb, demonstrated greater concentrations of plasma MMP-3 and IL-6, as well as serum type-II collagen turnover, indicating early interactions between mechanical joint loading and metabolic processes that may influence the future breakdown of cartilage and future KOA onset. In a small intervention study (n ¼ 16), changes to serum level of C1,2C and CS846 in response to a 30-min walk in patients with medial KOA was evaluated 52 . Regional cartilage thickness changes were measured from MRI obtained at study entry and at 5-year follow-up.…”
Section: Understanding the Biology Of Joint Deteriorationmentioning
confidence: 99%
“…The properties examined here were well motivated for a first systematic review in the framework of the relationship-based IJS model of OA pathophysiology and well developed in the literature. However, future reviews should consider other properties of the knee, such as inflammatory markers 57 , imaging-derived cartilage composition measures 58 , or markers of cartilage matrix turnover 59,60 , as these properties are also mechanosensitive and can be influenced by gait mechanics.…”
Section: Limitationsmentioning
confidence: 99%
“…15 A follow-up study of patients with medial knee OA indicated that changes to CS846, a marker of cartilage matrix synthetic activity, predicted cartilage thickening in the less involved lateral compartment. 16 Similar elevations of CS846 were present in a subset of patients 2 years after ACLR. These data support the need to evaluate OA risk and rehabilitation outcomes by assessing the interplay among structure, biology, and mechanics after ACL injury.…”
mentioning
confidence: 73%
“…14 Finally, serum biochemical biomarkers may play a role in the clinical assessment of OA disease states and OA risk. Previous researchers 15,16 showed that the change in serum biomarkers in response to a mechanical challenge provided insight into OA disease states. Specifically, changes to serum cartilage oligomeric matrix protein after a 30-minute walk predicted cartilage-thickness changes 5 years later in patients with knee OA.…”
mentioning
confidence: 99%